Characterization of a WAS splice-site variant in a patient with Wiskott-Aldrich syndrome - Toriello, Elisabetta; Maritato, Rosa; De Rosa, Antonio; Esposito, Maria Valeria; Damiano, Carla; Rosano, Carmen; Cirillo, Emilia; Tarallo, Antonietta; Abagnale, Cosimo; Cillo, Francesca; Romano, Roberta; Grilli, Laura; et al. (Frontiers in Immunology, 2025)
Wiskott-Aldrich syndrome (WAS) (MIM #301000) is a rare X-linked primary immunodeficiency due to mutations in the WAS gene, characterized by thrombocytopenia with small platelets, eczema, recurrent infections, and an increased incidence of autoimmunity and malignancies. A wide spectrum of mutations has been identified in the WAS gene responsible for a broad variety of clinical phenotypes. By using targeted next-generation sequencing (t-NGS), we identified in a 2-month-old boy with thrombocytopenia and immunological alterations a 4-nucleotide deletion from position +3 to +6 of intron 8 (c.777 + 3_777 + 6delGAGT) of WAS, currently classified on ClinVar as a variant of uncertain significance. The in-vitro characterization of the variant revealed the complete retention of intron 8 in the mature transcript, suggesting a splicing defect due to the loss of a splice donor site at the 5′-end of intron 8. By sequencing the polymerase chain reaction product, we identified a premature stop at codon 269; thus, consequently, no Wiskott-Aldrich syndrome protein (WASp) was detectable in peripheral blood mononuclear cells from the patient. Due to the total absence of a full-length WASp, it is expected that the patient will develop the severe form of the disease, although further monitoring is needed to better define his phenotype.